FACTORS ASSOCIATED WITH HYPERGLYCEMIA IN HOSPITALIZED NEONATES AT THAI NGUYEN NATIONAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To analyze factors associated with hyperglycemia in neonates hospitalized at Thai Nguyen National Hospital during 2024-2025.Research and methods: A cross-sectional descriptive study was conducted on 384 neonates admitted within the first 72 hours after birth. Maternal and neonatal factors were analyzed using univariate and multivariate logistic regression, with a significance threshold of p < 0.05.Results: Among 384 neonates, 43 children (11.2%) developed hyperglycemia. Significant associated factors included invasive respiratory support (OR = 7.24; p < 0.001), hypoalbuminemia (OR = 9.58; p = 0.013), hyponatremia (OR = 3.58; p = 0.045), and glucose infusion rate ≥ 6 mg/kg/min (OR = 1.94; p = 0.038).Conclusions: Neonatal hyperglycemia reflects metabolic disturbances in severe illness and intensive care conditions. Regular blood glucose monitoring, appropriate adjustment of glucose infusion rates, and early correction of metabolic imbalances may help prevent and improve outcomes in high-risk neonates.
Keywords: Hyperglycemia, neonate, associated factors.